2009
DOI: 10.3354/meps08033
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and sources of variation in flowering, seed supply and seedling recruitment in surfgrass Phyllospadix torreyi

Abstract: Knowledge of patterns and sources of variation in adult reproduction and juvenile recruitment is essential for understanding the dynamics of populations and their capacity to recover from disturbances. In-depth knowledge of this kind is lacking for many species of seagrass. Here we examined the degree to which temporal and spatial variation in seedling density in the surfgrass Phyllospadix torreyi was explained by the local production and deposition of seeds. We did this by measuring floral density, seed produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Reed et al (2009) demonstrated a similar correlation between reproductive structures and seed numbers in Phyllospadix torreyi. Seagrass canopies increase particle retention (Hendriks et al, 2010), so the presence of mature plants is likely to increase the retention of seeds as well as the sediment that may retain them even after the mature plants die back.…”
Section: Discussionmentioning
confidence: 69%
“…Reed et al (2009) demonstrated a similar correlation between reproductive structures and seed numbers in Phyllospadix torreyi. Seagrass canopies increase particle retention (Hendriks et al, 2010), so the presence of mature plants is likely to increase the retention of seeds as well as the sediment that may retain them even after the mature plants die back.…”
Section: Discussionmentioning
confidence: 69%
“…Female-biased sex ratios have been documented for the genus Phyllospadix (Williams 1995, Shelton 2008, 2010b, and recent work has shown that sex ratios can vary among spatially segregated populations (Addison 2009, Reed et al 2009. A variety of mechanisms may produce skewed sex ratios of flowering shoots, including spatial segregation of the sexes, non-random production of gender, or differential mortality or growth.…”
Section: Introductionmentioning
confidence: 99%
“…Most populations of Phyllospadix spp. are female-biased (see below), but seed production estimates range widely, from nearly 100% successful (Williams 1995, Reed et al 2009) to nearly 100% failed (Shelton 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations